A Comparative Analysis of Transformer-less Inverter Topologies for Grid-Connected PV Systems: Minimizing Leakage Current and THD - Shashwot Shrestha; Rachana Subedi; Swodesh Sharma; Sushil Phuyal (KEC Journal of Science and Engineering, 2025)
The integration of distributed energy resources (DERs), particularly photovoltaic (PV) systems, into the power grids have gained major attention due to their environmental and economic benefits. Although traditional transformer-based grid-connected PV inverter provides galvanic isolation for leakage current, it suffers from major drawbacks of high cost, lower efficiency, and increased size. Transformer-less grid-connected PV inverter (TLGI) has emerged as a prominent alternative as this achieves higher efficiency, compact design, and lower cost. However, due to a lack of galvanic isolation, TLGI is highly affected by the leakage current caused by the fluctuation of common mode voltage (CMV). This paper investigates three topologies —H4, H5, and HERIC—with the comparisons between their CMV, differential mode voltage (DMV), total harmonic distortion (THD), and leakage current. A simulation was done for each topology in MATLAB(Simulink) R2023a and the results from the simulation demonstrate that the H5 topology achieves a balance between low leakage current, reduced THD, and optimal operational efficiency, making it suitable for practical application.